Tough toad ahead: ontogenetic variation in thermal tolerance defines life-stage vulnerability in Duttaphrynus melanostictus - Pushkar Wagh; Saumitra Dhere; Maria Thaker; Kadaba Shamanna Seshadri (Journal of Thermal Biology, 2026)

How distinct are sleep sites from active sites across habitat types in lizards? - Nitya Prakash Mohanty; Anbazhagan Abinesh; Saumitra Dhere; Maria Thaker (Behavioral Ecology and Sociobiology, 2026)
Sleep poses constraints, such as increased vulnerability to predators, that can lead to differences in the use of habitat components across the diel cycle. However, very few studies have systematically evaluated site use of animals across both active and sleep phases. We quantified site use during the active and sleep phases in 412 individuals of eight species (six genera) of agamid lizards, from four habitat types (arboreal, semi-arboreal, rupicolous and ground). Sleep sites differed for five out of the eight species, in all habitat types except rupicolous. Semi-arboreal and arboreal lizards slept on narrower and more compliant perches, likely to detect and avoid predators, whereas ground-dwelling lizards slept in sheltered sites that probably afford a stable thermo-hydric environment. For most species, sleep sites differed from active sites in only a few characteristics, indicating that lizards respond to the potential costs of sleep while being constrained by their morpho-functional abilities. We found equivocal pattens of lower variability of sleep sites compared to active sites, which may be due to low variability in perch options or low costs of sleep in some habitat types. This study provides a large-scale test of diel shifts in habitat use and highlights the need to integrate sleep microhabitat use into ecological and conservation research.

Anuran assemblage in a rapidly urbanizing City in South Asia - K. S. Seshadri; M. K. Vidisha; Pushkar Ravindra Wagh; H. S. Sudhira; Maria Thaker (Urban Ecosystems, 2025)

Are Human Super‐Predators Always Super‐Scary? A Meta‐Analysis of Wild Animal Behavioural Responses to Human Interactions - Shawn Dsouza; Kartik Shanker; Maria Thaker (Ecology Letters, 2025)
Humans interact with wild animals through lethal and non‐lethal activities. While theory predicts that these interactions should alter animal behaviour, the relative magnitude of impact is not well understood. We conducted a systematic review and meta‐analysis of the past 30 years of research, focusing on changes in foraging, vigilance and movement behaviours in wild animals. We found that lethal human activities (e.g., hunting) cause significant behavioural changes, with targeted species increasing vigilance and reducing foraging in affected areas. Active non‐lethal activities (e.g., tourism) elicited similar but weaker patterns, with many species showing little to no change in their behavioural responses. In contrast, passive non‐lethal interactions (e.g., roads) produced highly variable responses. Overall, human‐induced fear elicits responses in wild animals that broadly align with predictions from the risk allocation hypothesis. However, the magnitude and direction of animal responses depend on the type of human activity and the ecological context. The most pronounced behavioural changes occur where humans pose a direct lethal threat. Gaps in the literature, uneven data within and across species, and limited information on the history or context of interactions currently limit our ability to better predict when and why animals change their behaviour in response to humans.

When humans shield predators from danger - Maria Thaker; Abi T. Vanak (Trends in Ecology & Evolution, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Does the diversity of anuran iris patterns have an ecological function or is it just beauty in the eye of the beholder? - Kadaba Shamanna Seshadri; S. Gangothri; Maria Thaker (Evolutionary Ecology, 2024)

Morphological divergence, tail loss, and predation risk in urban lizards - Shashank Balakrishna; Madhura Sham Amdekar; Maria Thaker (Urban Ecosystems, 2021)

Urban lizards use sleep sites that mirror the structural, thermal, and light properties of natural sites - Nitya Prakash Mohanty; Mihir Joshi; Maria Thaker (Behavioral Ecology and Sociobiology, 2021)

Diet influences latitudinal gradients in life‐history traits, but not reproductive output, in ectotherms - Udita Bansal; Maria Thaker (Global Ecology and Biogeography, 2021)
Aim Latitudinal gradients in life‐history traits are apparent in many taxa and are expected to be strong for ectotherms that have temperature‐driven constraints on performance and fitness. The strength of these gradients, however, should also be affected by diet. Because diet type (carnivory, omnivory, herbivory) influences accessibility to nutrition and assimilation efficiency, we aim to study how diet affects latitudinal gradients in lifetime reproductive output and the underlying life‐history traits in ectotherms. Location Global. Time period Recent. Major taxa studied Lizards (Reptilia, Squamata, Sauria). Methods We used empirical (352 species) and phylogenetically imputed data (563 species) to analyse the interactive effects of latitude and diet on life‐history traits (longevity, age at maturity, reproductive life span, hatchling mass, clutch/brood size, clutch/brood frequency, female mass) and lifetime reproductive output of lizards. Results Lifetime reproductive output does not significantly differ in lizards across diet types, and only carnivores exhibit a small increase at higher latitudes. Diet type, however, influences latitudinal patterns of individual life‐history traits. Carnivores exhibit a shift towards ‘slower‐paced’ life histories at higher latitudes for most traits (increased longevity, age at maturity, reproductive life span, and decreased clutch frequency). By contrast, herbivores either display ‘faster‐paced’ life histories (reduction in reproductive life span, hatchling mass, female mass) or no change (clutch frequency, clutch size, age at maturity) at higher latitudes. Omnivores exhibit intermediate and muted latitudinal patterns. Main conclusions We suggest that the nutritional challenges of herbivory, compounded by thermal constraints at higher latitudes, may explain differences in life‐history characteristics of herbivorous ectotherms. Intermediate patterns exhibited by omnivores highlight how flexibility in diet can buffer environmental challenges at higher latitudes. Our results indicate that lizards with different diet types display various trends in their life histories across latitudes, which eventually balance out to result in similar reproductive outputs throughout their lifetime, with little benefits to carnivory.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

A multivariate approach to understanding shifts in escape strategies of urban lizards - Anuradha Batabyal; Shashank Balakrishna; Maria Thaker (Behavioral Ecology and Sociobiology, 2017)

Moving to stay in place: behavioral mechanisms for coexistence of African large carnivores - Abi Tamim Vanak; Daniel Fortin; Maria Thaker; Monika Ogden; Cailey Owen; Sophie Greatwood; Rob Slotow (Ecology, 2013)
Most ecosystems have multiple predator species that not only compete for shared prey, but also pose direct threats to each other. These intraguild interactions are key drivers of carnivore community structure, with ecosystem‐wide cascading effects. Yet, behavioral mechanisms for coexistence of multiple carnivore species remain poorly understood. The challenges of studying large, free‐ranging carnivores have resulted in mainly coarse‐scale examination of behavioral strategies without information about all interacting competitors. We overcame some of these challenges by examining the concurrent fine‐scale movement decisions of almost all individuals of four large mammalian carnivore species in a closed terrestrial system. We found that the intensity of intraguild interactions did not follow a simple hierarchical allometric pattern, because spatial and behavioral tactics of subordinate species changed with threat and resource levels across seasons. Lions ( Panthera leo ) were generally unrestricted and anchored themselves in areas rich in not only their principal prey, but also, during periods of resource limitation (dry season), rich in the main prey for other carnivores. Because of this, the greatest cost (potential intraguild predation) for subordinate carnivores was spatially coupled with the highest potential benefit of resource acquisition (prey‐rich areas), especially in the dry season. Leopard ( P. pardus ) and cheetah ( Acinonyx jubatus ) overlapped with the home range of lions but minimized their risk using fine‐scaled avoidance behaviors and restricted resource acquisition tactics. The cost of intraguild competition was most apparent for cheetahs, especially during the wet season, as areas with energetically rewarding large prey (wildebeest) were avoided when they overlapped highly with the activity areas of lions. Contrary to expectation, the smallest species (African wild dog, Lycaon pictus ) did not avoid only lions, but also used multiple tactics to minimize encountering all other competitors. Intraguild competition thus forced wild dogs into areas with the lowest resource availability year round. Coexistence of multiple carnivore species has typically been explained by dietary niche separation, but our multi‐scaled movement results suggest that differences in resource acquisition may instead be a consequence of avoiding intraguild competition. We generate a more realistic representation of hierarchical behavioral interactions that may ultimately drive spatially explicit trophic structures of multi‐predator communities.

Costs and Benefits of the Presence of Leopards to the Sport‐Hunting Industry and Local Communities in Niassa National Reserve, Mozambique - AGOSTINHO A. JORGE; ABI T. VANAK; MARIA THAKER; COLLEEN BEGG; ROB SLOTOW (Conservation Biology, 2013)
Sport hunting is often proposed as a tool to support the conservation of large carnivores. However, it is challenging to provide tangible economic benefits from this activity as an incentive for local people to conserve carnivores. We assessed economic gains from sport hunting and poaching of leopards (Panthera pardus), costs of leopard depredation of livestock, and attitudes of people toward leopards in Niassa National Reserve, Mozambique. We sent questionnaires to hunting concessionaires (n = 8) to investigate the economic value of and the relative importance of leopards relative to other key trophy‐hunted species. We asked villagers (n = 158) the number of and prices for leopards poached in the reserve and the number of goats depredated by leopard. Leopards were the mainstay of the hunting industry; a single animal was worth approximately U.S.$24,000. Most safari revenues are retained at national and international levels, but poached leopard are illegally traded locally for small amounts ($83). Leopards depredated 11 goats over 2 years in 2 of 4 surveyed villages resulting in losses of $440 to 6 households. People in these households had negative attitudes toward leopards. Although leopard sport hunting generates larger gross revenues than poaching, illegal hunting provides higher economic benefits for households involved in the activity. Sport‐hunting revenues did not compensate for the economic losses of livestock at the household level. On the basis of our results, we propose that poaching be reduced by increasing the costs of apprehension and that the economic benefits from leopard sport hunting be used to improve community livelihoods and provide incentives not to poach . Costos y Beneficios de la Presencia de Leopardos para la Industria de la Caza Deportiva y las Comunidades Locales en Niassa, Reserva Nacional, Mozambique

Relative Impacts of Elephant and Fire on Large Trees in a Savanna Ecosystem - Graeme Shannon; Maria Thaker; Abi Tamim Vanak; Bruce R. Page; Rina Grant; Rob Slotow (Ecosystems, 2011)

Experimental examination of behavioural interactions between free-ranging wild and domestic canids - Abi Tamim Vanak; Maria Thaker; Matthew E. Gompper (Behavioral Ecology and Sociobiology, 2009)